THE USE OF GALLERY WALK TECHNIQUE TO ENHANCE STUDENTS READING COMPREHENSION - Bahtiar, Aqif Zulfakar; Erwin Akib; Wildhan Burhanuddin, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2020)
The objective of this research was to find out whether or not the implementation of gallery walk technique enhance reading comprehension in terms main idea and whether or not the implementation of gallery walk technique enhance reading comprehension in terms supporting details. The method used was pre-experimental method that used pre-test and post-test as an instrument of the research. The population of the research was the tenth grade of MA Bontomarannu that consisted of 20 students. The number of samples was 20 students. The data collection consisted of pre-test, treatment, and post-test. Forms of pre-test and post-test were try out that contained 10 words. The findings of the research showed that the students’ mean score of pre-test before treatment was 63.75%. While after treatment, the mean score of post-test was 97.5%. Therefore, the significant between pre-test and post-test was 52.94%. In order that, the researcher assumed that using gallery walk technique could enhance students reading comprehension